Implementasi Manajemen Strategik Syariah di BMT Amanah Ummah - Muna, Muhammad Niltal; Hapsari, Meri Indri (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
The aim of this research is to know implementation of Sharia Strategic Manajemen in BMT. The research object is BMT Amanah Ummah Surabaya. The research method used in this research are qualitative research, case study, and domain analysis, taksonomy analysis and componensial analysis. By using data collection technique such as interviewing and observing primary informant (BMT Amanah Ummah Management) and secondary informant (Sharia Supervisory Council) for data validity.The result of this research is the BMT Amanah Ummah has applied steps of sharia strategic management very well. Those adjustments can be seen from the steps of sharia strategic management start from strategy formulating, strategy implementing, and strategy evaluating. The indicators of this research are the process of strategic management done by BMT Amanah Ummah adjusted to Fred R. David concept, and the sharia principals used for process of sharia strategic management adjusted to maqashid sharia.